Comparative rural income distribution analysis for Brgy. Pungn Grande, Passi City and Brgy. Tubod, Bingawan, 1997 - Balane, Walter I .; Montemor, Ma. Reina G. (1999.)
This study was conducted in Brgy. Punong, Passi City and Brgy. Tubod, Bingawan. There were twenty four (24) respondents from Brgy. Punong, Passi City and fourty one (41) from Brgy. Tubod, Bingawan. The anlytical tools include the Income Decile, Gini-Coefficient and the Lorenz Curve., It was found out that income earners belonging to deciles in brgy. Punong, Passi City earn only 24.55 of the total annual household income earned for Brgy. Punong. While the upper deciles (6-10) earn 75.45 of the said income. On the other hand, the income earners belonging to deciles 1-5 in Brgy. Tubod, Bingawan earns 29.93 of the total the total household income earned for Brgy. Tubod Bingawan. While the other deciles earn 70.07 of the said income. It was observed that the income earners in the 10th decile earns 1,200 more than the income earners in the first decile in Brgy. Punong Passi City. On the other hand, the income earners in the 10th decile earns 506 greater than the income earners in the 1st decile income earners in Region VI and Philippines earns 2.2 and 1.7 respectively. In Brgy. Punong, Passi City and Tubod, Bingawan they earn 2.3 and 4.5 of the total annual hosehold income. The bigger percentages share the income earned by 1st decile income earners in brgy. Tubod, Bingawan is indicative of the barangays' greater advantage vis-a-vis income distribution equality compared to that of brgy. Punong, Passi City. It was found out that Passi City is Iloilo's highest income earner municipality.
Research Project (Undergraduate, Bachelor of Aarts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Barangay Punong, Passi City -- Income Distribution; Barangay Tubod, Bingawan -- Income Distribution